2001
DOI: 10.1124/mol.60.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Asp171and Asp262of the Chemokine Receptor CXCR4 Impairs Its Coreceptor Function for Human Immunodeficiency Virus-1 Entry and Abrogates the Antagonistic Activity of AMD3100

Abstract: The bicyclam AMD3100 is a highly potent and selective CXCR4 antagonist with strong antiviral activity against human immunodeficiency virus (HIV)-1 and HIV-2, which use CXCR4 as coreceptor for host cell entry. Here, we investigated the interaction of AMD3100 with CXCR4 at the molecular level by mutational analysis. We established a set of stably transfected U87.CD4 cell lines expressing different mutant forms of CXCR4 (i.e., CXCR4[WT], CXCR4[D171N], CXCR4[D262N], CXCR4[D171N,D262N], and CXCR4[H281A]), to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
118
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 32 publications
9
118
0
Order By: Relevance
“…Although V3 shows extensive amino acid diversity across HIV and SIV phylogeny, unlike V1/V2 and V4, which can tolerate insertions and deletions (4,10,22,46), the V3 length is highly conserved and is typically 34 or 35 amino acids (8,16,18,22). This conservation is consistent with the view that a critical V3 length is required to contact the chemokine receptor (22).Small-molecule inhibitors of CCR5 and CXCR4 have been described, which bind to a pocket defined by transmembrane helices (53) or membrane-proximal regions of the ECLs (17,19,58), respectively, and inhibit viral entry. Although their mechanism of action is not fully understood, rather than block-* Corresponding author.…”
supporting
confidence: 50%
“…Although V3 shows extensive amino acid diversity across HIV and SIV phylogeny, unlike V1/V2 and V4, which can tolerate insertions and deletions (4,10,22,46), the V3 length is highly conserved and is typically 34 or 35 amino acids (8,16,18,22). This conservation is consistent with the view that a critical V3 length is required to contact the chemokine receptor (22).Small-molecule inhibitors of CCR5 and CXCR4 have been described, which bind to a pocket defined by transmembrane helices (53) or membrane-proximal regions of the ECLs (17,19,58), respectively, and inhibit viral entry. Although their mechanism of action is not fully understood, rather than block-* Corresponding author.…”
supporting
confidence: 50%
“…Mutagenesis experiments suggest that the second extracellular loop, transmembrane IV, and transmembrane VI of CXCR4 are critical for its interaction with AMD3100 (47,48). In principle, this allows novel agonists to bind to the N terminus or to other regions of the receptor that are not necessary for antagonist(s) interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It shows activity against a wide variety of X4 and even R5/X4 HIV strains (20,(23)(24)(25)(26). Recently, our group demonstrated that two aspartate residues at positions 171 and 262 of the chemokine receptor CXCR4 are crucial for the high-affinity binding of AMD3100 to CXCR4 (27).…”
Section: Discussionmentioning
confidence: 99%